Hepcidin and iron status in elite female rugby players - Smith, S.; Black, K. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Hepcidin was identified as a negative regulator of iron levels in the early 2000s. Since then, the exercise-induced hepcidin response has been proposed as a mechanism of iron deficiency (ID) in athletes. By assessing and tracking haematological and inflammatory parameters in elite female rugby players, the aim of the current study is to describe the relationship between hepcidin and iron levels amongst elite female rugby players. Venepuncture blood samples were analysed from 17 elite female rugby players in February and July and analysed for iron, ferritin, soluble transferrin receptor, high sensitivity C-reactive Protein (CRP) and hepcidin. Dietary intakes, physical activity demands and DXA scans were also measured. Mean iron concentration in February was 21.3 ìmol/L and increased to 21.9 ìmol/L in July. Mean ferritin and sTfR values in February were 77.1 ìg/L and 2.62 mg/L respectively, and 75.1 ìg/L and 2.50 mg/L in July. Average CRP concentrations increased from 0.95 mg/L to 1.66 mg/L and mean hepcidin concentrations decreased from 34.2 ng/mL to 33.1 ng/mL. All mean variables were within the expected reference ranges, however some individual values fell outside this range. The exercise-induced hepcidin response may contributes to ID in elite female athletes, although more research is needed.